The becoming - Ng, Evelyn Nichaphan Miao Ling (2017)
The story behind The Becoming came when me and Shermaine was brainstorming for ideas for producing class. We asked ourselves what was one thing we felt strongly about. Being fresh back from our summer exchange in Korea, it was only natural that we went back to our trip for inspiration and one thing hit both of us almost spontaneously - Plastic Surgery. We shared with each other our encounters, how plastic surgery was so common and widely accepted by the nation. How it was so scary for the entire nation to be in such strong pursuits for mere perfection in beauty. And how it would be scarier if these pursuits manifests into a social norm. What turned out to be ideas for a module then turned into serious talks about a possible film for FYP. Sure it would be way easier to do a drama revolving around this idea, but why not try something we never tried before? Why not do something you wouldn’t be able to do before you graduate? Why not challenge ourselves for something a lot of Singaporean film-makers avoid? And thus, we took a courageous leap of faith and wrote something in the sci-fi world. In the process of doing so, we thought 2 directors might make sense since it was indeed a large project to handle. And hence, we decided to co-direct/write/edit together. The decision to co-direct seemed really natural because we have worked together for so many films, our ideas just seem to bounce off each other and most importantly we both have similar taste in films. Our past directing works have always been along the lines of darker themes, and most often explores the psyche of an individual. And this time round, we thought it would be interesting to challenge ourselves and take that to a higher level. We wanted to portray not just an individual but also a society, a society that is in mindless pursuit of beauty and perfection. We went on to explore the different beauty trends in the world such as having the V line jaw, the “fit a coin in your shoulder bones” trend, japan’s law on “being Fat” (yes Japan does have this law) to drinking collagen drinks and eating weird items like sheep’s placenta for beauty benefits. We were appalled and thought that it would be interesting to show a possible future whereby people are actually doing all of these, treating what we find crazy now as a norm. Because hey, if we continue this craze it might very well happen in the future right?